Determinan Keterikatan Kerja Akuntan Publik: Peran Kepuasan Kerja, Komitmen Organisasi, dan Budaya Organisasi - Ghina Nurjihan (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to examine the influence of Job Satisfaction, Organizational Commitment, and Organizational Culture on the Work Engagement of Public Accountants working in Public Accounting Firms (PAFs) located in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Greater Jakarta). The study employed a quantitative approach with a causal research design. The research population consisted of public accountants registered with the Center for Financial Profession Development (P2PK) of the Ministry of Finance of the Republic of Indonesia and the Indonesian Institute of Certified Public Accountants (IAPI). The sampling technique used was probability sampling with a simple random sampling method. Based on the Slovin formula, 307 respondents who met the research criteria were obtained. Data were collected using a five-point Likert scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS software. The results indicate that all proposed hypotheses were supported. Job Satisfaction had a positive and significant effect on Work Engagement, with a t-statistic of 10.738 (>1.96). Organizational Commitment also had a positive and significant effect on Work Engagement, with a t-statistic of 9.221 (>1.96), while Organizational Culture positively and significantly influenced Work Engagement, with a t-statistic of 6.594 (>1.96). The structural model explained 55.2% of the variance in Public Accountants' Work Engagement (R² = 0.552), indicating a moderate level of predictive power. This study contributes empirically to the organizational behavior literature by strengthening the Job Demands–Resources Theory within the context of the public accounting profession in Indonesia. Furthermore, the findings provide practical implications for Public Accounting Firms in designing human resource management strategies by enhancing job satisfaction, strengthening organizational commitment, and fostering a supportive organizational culture to improve auditors' work engagement and, ultimately, the quality of audit services.